GPGPU-Based Parallel Computation Using Discrete Elements in Geotechnics: A State-of-Art Review - Gujjala, Yashwanth Kumar; Kim, Hyung-Mok; Ryu, Dong-Woo (Archives of computational methods in engineering, 2023)
Large deformation near surface excavations and openings has been frequently simulated in geotechnical problems. Mesh-based approaches for large-scale simulation have long been the preferred method due to their capacity to handle real-world domain sizes and processing advantage over particle-based methods. Particle-based methods, on the other hand, are better at mimicking local straining processes like fracturing. Moreover, field-scale numerical simulations based on discrete element based approaches have become possible thanks to the rapid development of graphical processing unit (GPU) cores for general purpose computing over the last decade. As graphics cards are now found in nearly all personal computer (PC)s, the vast majority of researchers may take advantage of their processing capability and create parallelism in their code while reducing computational time. However, most of the GPU cards are based on single precision which are not suitable for double precision computation required in solving geotechnical mechanisms. Hence, selection of a suitable graphic card is also vital in achieving the desired simulation. The goal of this study is to summarize existing research on the types of geotechnical issues addressed via application of general-purpose computing of graphical processing unit (GPGPU), as well as address the difficulties encountered in implementing various numerical algorithms on the GPU architecture. The survey suggested that GPU based discrete element method and combined finite discrete element method are the most popular techniques for solving geomechanical issues due to their intrinsic numerical structure that is suited for parallelization.